Measuring Efficiency of Health Systems in the Eastern Mediterranean Region During COVID-19 Using Data Envelopment Analysis Method (DEA) - Khelassi Abdel-illah; Rezgui Nour Elhouda; Besir Lutfi (Journal of North African Economies, 2025)
This study aims at measuring the efficiency of health systems in the Eastern Mediterranean countries in facing the rapid spread of the COVID-19 during the first year of its expansion in the region using data envelopment analysis (DEA) approach. We have adopted a set of variables that express inputs and outputs of the model (Health Expenditure per Capita, Physicians per 10 000 population, Nurses and midwifes per 10 000 population, Hospital beds per 10 000 population) as input variables,(Recovery Rate) as output variables.The study concludes that the studied Eastern Mediterranean countries achieved different levels of efficiency from one country to another, in that the efficiency is not always linked to high income and increased supply, but rather to optimal utilization of resources.